2021
DOI: 10.2147/ijgm.s271635
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Histopathological Representation of Excessive Proliferation of Trophoblast Cells with the Possibility of Malignant Events After Complete Hydatidiform Mole

Abstract: Introduction: Fifteen to twenty percent of the patients with complete hydatidiform mole transform malignancy into gestational trophoblastic tumors. The marked proliferation of trophoblastic cells is one of the characteristics that determines high risk for the occurrence of post-hydatidiform mole malignancy. The objective of the study was to analyze the histopathologic feature of the marked proliferation of trophoblastic cells as a role in posthydatidiform mole malignancy that can be used as a determinant of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
0
0
Order By: Relevance
“…A study by Irianti (2000) showed that there were about 15-20% of hydatidiform moles turned into a malignant gestational trophoblastic tumor (GTN), even though a suction curettage had been performed [31]. This is in line with the results of a study by Tobing (2021) which showed that there was a significant difference in the histopathology of complete hydatidiform moles (73.5%) [37]. The theory proposes that a complete hydatidiform mole with excessive hyperplasia tends to turn into malignancy in the later course of the disease, which is characterized by loss of growth control.…”
Section: Length Of Stay Duration Of Treatment An Interval Of Pregnanc...supporting
confidence: 62%
“…A study by Irianti (2000) showed that there were about 15-20% of hydatidiform moles turned into a malignant gestational trophoblastic tumor (GTN), even though a suction curettage had been performed [31]. This is in line with the results of a study by Tobing (2021) which showed that there was a significant difference in the histopathology of complete hydatidiform moles (73.5%) [37]. The theory proposes that a complete hydatidiform mole with excessive hyperplasia tends to turn into malignancy in the later course of the disease, which is characterized by loss of growth control.…”
Section: Length Of Stay Duration Of Treatment An Interval Of Pregnanc...supporting
confidence: 62%
“…In Western countries, the incidence of hydatidiform mole ranges from 1:1,450 to 1:2,000 pregnancies, while choriocarcinoma occurs in 1:14,000 to 1:40,000 pregnancies. Furthermore, the prevalence of GTD is reportedly higher in developing countries [2]. Hydatidiform mole occurs in 1:51 to 1:141 pregnancies in Indonesia, and 1:28 to 1:105 pregnancies in West Java [3].…”
Section: Introductionmentioning
confidence: 99%